RESPONSE OF WHEAT TO DIFFERENT ABIOTIC STRESS CONDITIONS: A REVIEW - Harikala Paudel; Radhakrishna Bhandari; Anjali Dhakal; Shivalal Nyaupane; Binod Panthi; Mukti Ram Poudel (Science Heritage Journal)
Wheat serves as the number one crop for ensuring food and nutritional security in the world. The production and productivity of wheat have been greatly influenced by global warming and climate change which have created environments such as drought, heat stress, and saline conditions. To address the advances in the study of the response of wheat against such climatic implications, this review was done. Abiotic stress mainly affects the morphology, phenology, and physiology of wheat. Abiotic stress induces reactive oxygen species (ROS) in wheat causing a reduction in root, shoot, and reproductive growth. Impact on important yield-related traits such as spike length, grains per spike, grain weight, thousand-grain weight, and reduces the yield of wheat. The plant has earliness as a phenological, rolling of leaves as morphological, waxiness as physiological, and production of heat shock proteins and proline content as a biochemical defense. A proper study of these effects and responses at the genetic and molecular level is necessary to cope with the existing yield gap in a farmer’s field as compared to normal conditions. The study of wheat against such circumstances would help plant breeders identify stress-tolerant genotypes that could significantly contribute to eradicating existing hunger and malnutrition in the world.